Improvement of Human Resources Performance in the Corporate Environment with Gamification Concept - Friska Siallagan, Anna Rahmalia Andres, Emil R. Kaburuan (International Journal of Control and Automation, 2020)
Technological advances have influenced many aspects of human life. Appropriate use of technology will help improve the efficiency and effectiveness of a process and maximize its output. In this article the author wants to create the concept of gamification that companies use to improve the performance of human resources. In designing the gamification, the writer uses the MDA framework, namely Mechanics, Dynamics, and Aesthetics.